(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2020)
Discourses of Southeast Asia is a volume published as part of the M.A.K. Halliday Library Functional Linguistics Series, so named as Halliday is regarded as the founding father of Systemic Functional Linguistics (Pakir 2019). The volume is made up of an introduction by the editors and 12 chapters by contributors who draw on Systemic Functional Linguistics (SFL) to examine texts and events in the region. SFL approaches language as a societal phenomenon and therefore calls for the analysis of language in context. For this reason, SFL provides an ideal framework for discourse analysts to examine semiotic engagements and the construction of meaning through interaction. However, applying SFL theory in discourse analysis requires careful consideration of how lexicogrammatical choices can be made from the resources available in a language.